Recurrence timing and patterns incorporating lymph node status after neoadjuvant chemoradiotherapy plus esophagectomy for esophageal squamous cell carcinoma - Liu, Guihong; Hu, Binbin; Chen, Tao; Zhang, Xin; Tang, Yu; Chen, Qian; Shi, Huashan (Frontiers in Oncology, 2024)
Purpose: About 40% of esophageal squamous cell carcinoma (ESCC) patients experienced recurrence after neoadjuvant chemoradiotherapy (nCRT) plus esophagectomy. While limited information was available on recurrence risk stratification in ESCC after neoadjuvant treatment. Our previous study showed ypN status was a reliable tool to differentiate and predict the prognosis in the recurrent population. Here, we evaluated recurrence timing and patterns in ESCC patients, taking into consideration lymph node status after nCRT.A total of 309 ESCC patients treated with nCRT plus esophagectomy between 2018 and 2021 were enrolled in this observational cohort study. Lymph node status was recorded by the pathologist according to the surgical specimens. We retrospectively investigated the timing and patterns of recurrence and the prognoses in ESCC patients, taking into consideration lymph node status after nCRT.Results: After nCRT plus surgery in ESCC patients, lymph node metastasis was associated with unfavorable clinicopathological factors and high risks of recurrence. In the recurrent subgroup, ypN+ patients experienced earlier recurrence, especially for locoregional recurrence within the first year. Moreover, ypN+ patients had poorer prognosis. However, the recurrence patterns in the ypN-and ypN+ groups were similar. Besides, there were no significant differences in surgery to recurrence, recurrence to death, or overall survival among patients with locoregional or distant recurrence for overall patients and within ypN-or ypN+ groups.Conclusions: Lymph node metastasis was correlated with unfavorable clinicopathological factors and high risks of recurrence. Despite a similar recurrence pattern in the recurrent subgroup between the ypN-and ypN+ groups, ypN+ patients exhibited earlier recurrence and a worse prognosis.